2020
DOI: 10.5194/acp-20-7843-2020
|View full text |Cite
|
Sign up to set email alerts
|

Attributing ozone and its precursors to land transport emissions in Europe and Germany

Abstract: Abstract. Land transport is an important emission source of nitrogen oxides, carbon monoxide, and volatile organic compounds. The emissions of nitrogen oxides affect air quality directly. Further, all of these emissions serve as a precursor for the formation of tropospheric ozone, thus leading to an indirect influence on air quality. In addition, ozone is radiatively active and its increase leads to a positive radiative forcing. Due to the strong non-linearity of the ozone chemistry, the contribution o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 102 publications
4
29
0
Order By: Relevance
“…Similar un- 2020) who applied CAMx coupled offline to WRF using almost identical emissions over roughly the same domain, as well as previously by Huszar et al (2018a, b) and Huszar et al (2020a) too. The modeled negative PM 2.5 bias can be attributed to the underestimation of aerosol components like nitrates and organic aerosol, as seen -similarly to our results -in Schaap et al (2004) and Myhre et al (2006). However, besides underestimated emission inventory values, daytime dilution that is too strong and overestimated vertical turbulence can probably play a role too, as argued by Nopmongcol et al (2012).…”
Section: Discussionsupporting
confidence: 83%
“…Similar un- 2020) who applied CAMx coupled offline to WRF using almost identical emissions over roughly the same domain, as well as previously by Huszar et al (2018a, b) and Huszar et al (2020a) too. The modeled negative PM 2.5 bias can be attributed to the underestimation of aerosol components like nitrates and organic aerosol, as seen -similarly to our results -in Schaap et al (2004) and Myhre et al (2006). However, besides underestimated emission inventory values, daytime dilution that is too strong and overestimated vertical turbulence can probably play a role too, as argued by Nopmongcol et al (2012).…”
Section: Discussionsupporting
confidence: 83%
“…In addition to the issues described above, outstanding issues around the representation of the transport of ozone in models remain. These issues have been assessed recently in the context of the effect of model grid resolution on simulations that tag ozone production to different sources of ozone precursors (Mertens et al, 2020). Mertens et al (2020) have shown that contributions from anthropogenic emissions averaged over large scales (1,000 km) are quite robust with respect to model resolution but that contributions from stratospheric ozone transported to the surface differ strongly between models of different resolution.…”
Section: Impacts Of Dynamical Variability On the Ozone Burden And Budgetmentioning
confidence: 99%
“…These issues have been assessed recently in the context of the effect of model grid resolution on simulations that tag ozone production to different sources of ozone precursors (Mertens et al, 2020). Mertens et al (2020) have shown that contributions from anthropogenic emissions averaged over large scales (1,000 km) are quite robust with respect to model resolution but that contributions from stratospheric ozone transported to the surface differ strongly between models of different resolution. They ascribe the reason for this to differences in the efficiency of mixing in the vertical and emphasize that studies that perform attribution of ozone to source sectors should account for the stratospheric ozone source explicitly in order to better understand intermodel differences.…”
Section: Impacts Of Dynamical Variability On the Ozone Burden And Budgetmentioning
confidence: 99%
“…Tropospheric ozone plays a central role in the chemistry and self-cleansing capacity of the troposphere (Crutzen, 1973;Monks et al, 2015); however, at high concentrations close to the ground, it is harmful to human health (Haagen-Smit, 1952;Fleming et al, 2018) and vegetation (Reich and Amundson, 1985;Mills et al, 2018). As well as being transported into the troposphere through exchange with the stratosphere, ozone can be formed via chemical reactions in the troposphere involving two chemically distinct precursors: oxides of nitrogen (collectively NO x ) and reactive carbon species, including carbon monoxide, methane, and volatile organic compounds (Crutzen, 1973;Atkinson, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Tagging and perturbation are complementary approaches (Clappier et al, 2017;Thunis et al, 2019;Mertens et al, 2020). While tagging delivers information about the contribution of different emission sources to a pollutant of interest, perturbation studies deliver information about the sensitivity of pollutants to changes in emissions, including changes in the chemical lifetimes of pollutants in response to variations in emissions.…”
Section: Introductionmentioning
confidence: 99%